1996
DOI: 10.1007/bf02583292
|View full text |Cite
|
Sign up to set email alerts
|

Motion-onset visual evoked potentials improve the diagnosis of glaucoma

Abstract: Chronic glaucoma has been shown preferentially to damage larger retinal cells and optic nerve fibres that provide the input to the magnocellular visual pathway. We compared the motion-onset visual evoked potentials (primarily the magnocellular system) with those to standard pattern reversal in 20 patients with bilateral chronic glaucoma. For motion-onset visual evoked potentials, the pattern (isolated 40' checks of 10% contrast) moved in four cardinal directions (varied randomly from trial to trial) at a veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Nevertheless, the idea that glaucoma might be detected using motion VEPs attracted interest. Results by Kubová et al [110] suggest that the amplitude of the N2 is hardly affected by chronic glaucoma, while the latency appears to be a more sensitive indicator of glaucoma than the pattern-reversal P100 latency. In a study by Korth et al [123] both amplitude and latency were affected in patients with open-angle glaucoma.…”
Section: Glaucomamentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, the idea that glaucoma might be detected using motion VEPs attracted interest. Results by Kubová et al [110] suggest that the amplitude of the N2 is hardly affected by chronic glaucoma, while the latency appears to be a more sensitive indicator of glaucoma than the pattern-reversal P100 latency. In a study by Korth et al [123] both amplitude and latency were affected in patients with open-angle glaucoma.…”
Section: Glaucomamentioning
confidence: 95%
“…Therefore, in some studies a 'virtual electrode' was introduced corresponding to the occipito-temporal electrode with the largest response as determined individually for each subject [e.g., 42, 107,110].…”
Section: Stimulation Schemesmentioning
confidence: 99%
“…One subdivision of the visual system, known as the magnocellular (M) pathway, begins at the level of the ganglion cells in the retina, projects through the M layers of the lateral geniculate nucleus, and terminates in the primary visual cortex (V1) (3,4). There are several lines of evidence for an M pathway deficit in dyslexia, including abnormally small cells in the M layers of the LGN (5), impaired perceptual performance (6)(7)(8)(9)(10)(11), and reduced electrophysiological responses (5,(12)(13)(14) to stimuli processed mainly by the M pathway. Furthermore, a recent functional MRI (fMRI) study (15) reported that dyslexics showed essentially no significant activity in a cortical visual area (MTϩ that consists of area MT along with adjacent motion sensitive areas) that is believed to receive a strong M pathway input.…”
mentioning
confidence: 99%
“…4 ], in agreement with the literature that shows that this mechanism is usually selectively affected by this pathology. [ 20 21 22 23 24 25 26 27 28 29 ] With the G2 patient, all perimetric tests exhibit significant losses in MD and the shape of the visual field is also abnormal [ Fig. 5 ].…”
Section: Resultsmentioning
confidence: 99%